2020
DOI: 10.1093/jac/dkaa262
|View full text |Cite
|
Sign up to set email alerts
|

Catheter-related bloodstream infections: predictive factors for Gram-negative bacteria aetiology and 30 day mortality in a multicentre prospective cohort

Abstract: Background Catheter-related bloodstream infections (CRBSIs) increase morbidity and mortality, prolong hospitalization and generate considerable medical costs. Recent guidelines for CRBSI recommend empirical therapy against Gram-positive bacteria (GPB) and restrict coverage for Gram-negative bacteria (GNB) only to specific circumstances. Objectives To investigate predictors of GNB aetiology in CRBSI and to assess the predictor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 18 publications
0
20
0
5
Order By: Relevance
“…In the last years, a shift towards a progressive increase in GNB in the overall BSI episodes in oncohematological patients has been described [12,[19][20][21], with some studies reporting even a predominance of GNB [22][23][24]. Additionally, some studies have identified neutropenia to be an independent risk factor for presenting a CRBSI caused by GNB [25]. The specifical changes reported in this study, with a progressive linear increase in the percentage of GNB among CRBSIs in neutropenic patients, as well as in other CRBSI studies in the general population [13,26,27], might be at least partially explained by the increasing age and complexity of patients.…”
Section: Plos Onementioning
confidence: 99%
“…In the last years, a shift towards a progressive increase in GNB in the overall BSI episodes in oncohematological patients has been described [12,[19][20][21], with some studies reporting even a predominance of GNB [22][23][24]. Additionally, some studies have identified neutropenia to be an independent risk factor for presenting a CRBSI caused by GNB [25]. The specifical changes reported in this study, with a progressive linear increase in the percentage of GNB among CRBSIs in neutropenic patients, as well as in other CRBSI studies in the general population [13,26,27], might be at least partially explained by the increasing age and complexity of patients.…”
Section: Plos Onementioning
confidence: 99%
“…In the training cohort, 575 (15%, 95% confidence interval (CI) [ 14 16 ]) catheters were colonized. Among 597 catheters removed for suspected CRI, 477 (80%, 95% CI [77–83]) were culture-negative.…”
Section: Resultsmentioning
confidence: 99%
“…Similar results were observed in a prospective observational study by Lorente et al [ 13 ]. On the other hand, the absence of focus eradication (i.e., CVC removal) is clearly associated with mortality in the setting of CRBSI [ 14 16 ]. Consequently, the decision to remove the CVC is generally left at the physician’s judgement and experience.…”
Section: Introductionmentioning
confidence: 99%
“…This is a post hoc analysis of the PROBAC project, a prospective, observational, multicenter cohort study, including consecutive patients with bloodstream infections (BSI) admitted to 26 Spanish hospitals from October 2016 to March 2017; the design and inclusion criteria have been described elsewhere ( 8 , 17 ).…”
Section: Methodsmentioning
confidence: 99%